The Influence of Scarcity Persuasion and Price Perception on Online Impluse Buying: Mediating Role of Aurosal - Monika Dini Landria; Widhy Tri Astuti; Titik Kusmantini (CV. Doki Course and Training, 2026)
This study examines the influence of scarcity persuasion and price perception on online impulse buying behaviour among consumers of Skintific skincare products during TikTok Live sessions, with arousal acting as a mediating variable. Employing a quantitative approach, data were collected from 170 respondents who had purchased Skintific products through TikTok’s live streaming feature, and analysed using SEM-PLS with SmartPLS 4.1. The findings reveal that scarcity persuasion has a positive and significant effect on impulsive buying, whereas price perception shows no significant direct effect. Furthermore, both scarcity persuasion and price perception significantly enhance arousal; however, arousal does not significantly influence impulsive buying and therefore does not mediate either relationship. These results indicate that although live streaming can elevate consumers’ emotional activation, purchasing decisions for skincare products remain predominantly rational. The study reinforces the effectiveness of time- and quantity-based scarcity strategies in stimulating impulsive purchasing within live commerce